2018
DOI: 10.1029/2018jc014109
|View full text |Cite
|
Sign up to set email alerts
|

Field Observations of Alongshore Runup Variability Under Dissipative Conditions in the Presence of a Shoreline Sandwave

Abstract: Video measurements of runup were collected at low tide along several profiles covering an alongshore distance of 500 m. The morphology displayed a complex shape with a shoreline sandwave in the lower beach face of about 250 m long mirrored in the inner sandbar. Wave conditions were stationary and moderate (offshore height of 2 m and peak period of nearly 13 s) but yet dissipative. Runup energy was dominated by infragravity frequencies. Alongshore variations in runup (by a factor up to 3) observed both in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 68 publications
(141 reference statements)
0
4
0
1
Order By: Relevance
“…Some authors (Ruessink et al 1998;Guedes et al 2011;Senechal et al 2011) have argued that the use of a local parameter in a complex system (e.g., very different slopes in the swash and surf zones, or the presence of bars) may be misleading, and thus including beach slope does not improve the predictions. Senechal et al (2018) found that the beach morphology in the inner surf zone has a greater influence than the beach face slope, since surf zone morphology modifies the incident wave patterns over a short crossshore distance. Our results agree with this observation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Some authors (Ruessink et al 1998;Guedes et al 2011;Senechal et al 2011) have argued that the use of a local parameter in a complex system (e.g., very different slopes in the swash and surf zones, or the presence of bars) may be misleading, and thus including beach slope does not improve the predictions. Senechal et al (2018) found that the beach morphology in the inner surf zone has a greater influence than the beach face slope, since surf zone morphology modifies the incident wave patterns over a short crossshore distance. Our results agree with this observation.…”
Section: Discussionmentioning
confidence: 97%
“…Using a numerical model, Guza and Feddersen (2012) found that including the frequency spread offshore f s,0 and directional spread σ θ on run-up parameterizations at the infragravity band reduced the scatter on run-up predictions. The influence of nearshore morphology (such as surf/swash zone interactions) and longshore variability (e.g., the presence of beach cusps) have been identified to also play an important role in swash excursion dynamics (Masselink and Puleo 2006;Bryan and Coco 2010;Senechal et al 2018;Almar et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thème 1 -Hydrodynamique marine et côtière HUGUES et al, 2014, SENECHAL et al, 2018. Thème 1 -Hydrodynamique marine et côtière…”
Section: Analyses Des Donnéesunclassified
“…In addition, some recent studies consider runup during storm conditions (Fiedler et al., 2015; Senechal et al., 2011) and extreme runup (García‐Medina et al., 2020; Montoya & Lynett, 2018), or examine the role of infragravity motions (de Bakker et al., 2014; R. A. Holman & Bowen, 1984), and nearshore morphology (Cohn & Ruggiero, 2016; Hughes et al., 2014). A few recent studies (Guedes et al., 2012; Ruggiero et al., 2004; Senechal et al., 2018) further explore the alongshore variability of runup.…”
Section: Introductionmentioning
confidence: 99%